(3CUd GdCfhGYs - (3OGQhjf, TGQdR,s 1809-1882; (3GdedjLj, eLOj eMehOs; (3UGOb, SejQ MfGs ((3GdbGgQI (B:s (3GdeLdS GdCYdi ddKbGaI,s, 2004)
(3jJfGhd gPG GdcJGH ehVhYGJ eNJdaI aj Yde GdfaS eKd GdJOLjf hfXQjI GdGfJbGA GdWHjYj hGdZQjRI(B.s
Keywords: (3GdfThA hGdGQJbGAs